Ways To Choose Methods for Assessing the Effectiveness Of Investision Projects In Joint-Stock Companies Based On Criteria In Uzbekistan - Ulashov Aliboy Rashid ogli (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
This article examines the key conditions that influence the selection of methods for evaluating investment projects in joint-stock companies. Particular attention is given to economic, financial, and risk-related factors that determine the effectiveness of project appraisal. Based on a systematic analysis, the study develops scientifically grounded proposals and practical recommendations aimed at improving investment decision-making and enhancing the overall efficiency of capital allocation in joint-stock companies.